2017
DOI: 10.1080/09571264.2017.1324773
|View full text |Cite
|
Sign up to set email alerts
|

The premium price for Italian red wines in new world wine consuming countries: the case of the Russian market

Abstract: Italian wine is increasingly appreciated in new world consumer countries and, in particular, in Russia where consumers associate its consumption with an Italian lifestyle. In this paper, market value for wine search attributes is measured through the estimation of a hedonic price model using online data from a Wine Searcher website and the information contained in the labels of wines marketed in Russia. Results show a premium price for wines from Piedmont and Tuscany, and in particular for non-native varieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…Regarding reputation attributes, protected indicators of origin are significant and increase sales by 104.33%, extending to China the study of Galati et al (2017), which showed a positive effect of designations of origin for the Russian market. Protected indicators of origin also enhance the importance of COO since they are strongly are connected to the production area.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding reputation attributes, protected indicators of origin are significant and increase sales by 104.33%, extending to China the study of Galati et al (2017), which showed a positive effect of designations of origin for the Russian market. Protected indicators of origin also enhance the importance of COO since they are strongly are connected to the production area.…”
Section: Resultsmentioning
confidence: 86%
“…The lowest prices are those of Argentinian Alcohol content does not represent a significant variable, confirming results by Angulo et al (2000) for the Spanish market. On the contrary, alcohol has found to be significant in the Russian market (Galati et al, 2017), denoting a different consumers' taste.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, it seems remarkable the role of 'alcohol content' variable that in our study was not statistically significant in affecting additional price for organic wine. Conversely, 'alcohol content' positively affects the prices of conventional wine (Galati et al, 2017). This result may suggest that the additional price for organic wine is not influenced by alcohol content, i.e.…”
Section: Resultsmentioning
confidence: 94%
“…Another study on willingness to pay (WTP) shows consumers' willingness to pay a premium price of 20% on organic salmon in Danish retail sale (Ankamah-Yeboah et al, 2016) Furthermore, a study on Italian wine showed the willingness of Russian consumers to pay a premium price on Italian red wines (mainly Piedmontese and Tuscan wines) and IGT and IGP wines (Galati et al, 2017).…”
Section: Country Of Originmentioning
confidence: 99%